Flood Hotspot Monitoring System and Navigation Application - Ramasamy, Kerrain; Ghafar, Aimi Syamimi (Progress in Engineering Application and Technology, 2023)
The issue of flood in some areas because of unimproved road infrastructures and environmental aberrations and poor drainage system are challenges encountered on roadways. To overcome these problems, a study has been conducted to develop an application called Flood Hotspot Monitoring System and Navigation Application that can display the information of water levels, temperature, relative humidity, rain status, and the location of the node and also read data of route suggestion from google sheet. Furthermore, it can navigate users in the application by using turn by turn navigation features. The application is designed using MIT app inventor to display the rain status, water level, temperature, relative humidity, and read data of route suggestion from google sheet and navigate the user. On top of that, the application is programmed using a block-based programming language. The ability of the system is tested and the output of flood monitoring and the route suggestion to the selected destination is displayed on the smartphone together with the text direction shown in the list view. On top of that, the SUS questionnaire has been conducted to test the validation of system. Hence, the average SUS score achieved is 74.5/100 and this demonstrates that utilizing the application is acceptable